Neural correlates of formal thought disorder: An activation likelihood estimation meta‐analysis. Issue 10 (27th June 2017) - Wensing, Tobias; Cieslik, Edna C.; Müller, Veronika I.; Hoffstaedter, Felix; Eickhoff, Simon B.; Nickl‐Jockschat, Thomas
Abstract: Formal thought disorder (FTD) refers to a psychopathological dimension characterized by disorganized and incoherent speech. Whether symptoms of FTD arise from aberrant processing in language‐related regions or more general cognitive networks, however, remains debated. Here, we addressed this question by a quantitative meta‐analysis of published functional neuroimaging studies on FTD. The revised Activation Likelihood Estimation (ALE) algorithm was used to test for convergent aberrant activation changes in 18 studies (30 experiments) investigating FTD, of which 17 studies comprised schizophrenia patients and one study healthy subjects administered to S‐ketamine. Additionally, we analyzed task‐dependent and task‐independent (resting‐state) functional connectivity (FC) of brain regions showing convergence in activation changes. Subsequent functional characterization was performed for the initial clusters and the delineated connectivity networks by reference to the BrainMap database. Consistent activation changes were found in the left superior temporal gyrus (STG) and two regions within the left posterior middle temporal gyrus (p‐MTG), ventrally (vp‐MTG) and dorsally (dp‐MTG). Functional characterization revealed a prominent functional association of ensuing clusters from our ALE meta‐analysis with language and speech processing, as well as auditory perception in STG and with social cognition in dp‐MTG. FC analysis identified task‐dependent and task‐independent networks for all three seed regions, which were mainly related to language and speech processing, but showed additional involvement in higher order cognitive functions. Our findings suggest that FTD is mainly characterized by abnormal activation in brain regions of the left hemisphere that are associated with language and speech processing, but also extend to higher order cognitive functions. Hum Brain Mapp 38:4946–4965, 2017 . © 2017 Wiley Periodicals, Inc.